Tensions between policy makers and general practitioners in implementing new genetics: grounded theory interview study - Kumar, Satinder (British Medical Journal, 1999)
OBJECTIVE: To explore general practitioners' perceptions of their role in implementing genetic technology. DESIGN: Grounded theory interview study. SETTING: Primary care. SUBJECTS: Purposive sample of 30 general practitioners with a further theoretical sample of 14. RESULTS: Inconsistencies were identified between policy makers' and general practitioners' definitions of general practitioners' role in implementing the new genetics. General practitioners emphasised the need to build on current practice, whereas policy makers focused on transforming practice to include the new specialised roles and skills. Two core themes were identified: genetics in a generalist context, which included appropriate generalist intervention, the ethical dilemmas implicit in the “therapeutic gap,” the familial-hereditary distinction in primary care, and the implications for generalist identity, including the potential marginalisation of generalism. CONCLUSION: New technologies such as genetics that require implementation in general practice should be integrated within existing generalist frameworks.